2004
DOI: 10.1038/sj.cgt.7700730
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific intravenous gene delivery using oncolytic adenoviruses

Abstract: In this report, we describe a vector system that specifically delivers transgene products to tumors following intravenous (i.v.) administration. The Escherichia coli cytosine deaminase (CD) gene was placed in the E3B region of the tumor-selective, replicationcompetent adenovirus ONYX-411, under the control of endogenous viral late gene regulatory elements. Thus, CD expression was directly coupled to the tumor-selective replication of the viral vector. In vitro, CD was expressed efficiently in various human can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
(36 reference statements)
1
35
0
Order By: Relevance
“…Transgene expression is restricted from Ad-14.7-GM and Ad-23K-GM viruses after intravenous administration in nude mice Previous studies have shown that expression of the transgenes can be targeted to the tumor but prevented in non-target organs such as the liver by linking transgene expression to viral replication, 15 thereby improving the safety profile of the vectors. To determine if inserting the transgene into the E3 or L3 regions results in a similarly improved safety profile as observed for the Ad-14.7K-GM or Ad-23K-GM vectors, an in vivo study was performed in which virus was injected into mice i.v.…”
Section: Construction Of Gm-csf Insertion Site Oncolytic Adenoviral Vmentioning
confidence: 99%
See 4 more Smart Citations
“…Transgene expression is restricted from Ad-14.7-GM and Ad-23K-GM viruses after intravenous administration in nude mice Previous studies have shown that expression of the transgenes can be targeted to the tumor but prevented in non-target organs such as the liver by linking transgene expression to viral replication, 15 thereby improving the safety profile of the vectors. To determine if inserting the transgene into the E3 or L3 regions results in a similarly improved safety profile as observed for the Ad-14.7K-GM or Ad-23K-GM vectors, an in vivo study was performed in which virus was injected into mice i.v.…”
Section: Construction Of Gm-csf Insertion Site Oncolytic Adenoviral Vmentioning
confidence: 99%
“…15,18 This tumor-specific transgene expression improves the safety of the vector. Several insertion sites, such as the E3A region 11,18,22 and E3B region, 15,18 were identified on the basis of detailed knowledge of transcription in adenoviruses. More recently, a novel transposonbased mechanism has been described that identified other potential insertion sites, even though the exact transcriptional regions had not been previously identified.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations